Evaluation of Complete Blood Count Parameters to Predict Abnormal Uterine Bleeding - Defne Ay Tuncel; Can Acıpayam (Children)
Background/Objectives: To investigate the diagnostic value of hematological parameters in adolescents with abnormal uterine bleeding (AUB), to make early diagnoses, and to prevent life-threatening bleeding. Methods: A total of 141 children, 70 patients, and 71 controls were included in the study. The laboratory findings of the patient and control groups were obtained from medical records. Cut-off values were estimated using constructing receiver operating characteristic (ROC) curves of complete blood count parameters to differentiate patients with AUB from control patients. Results: WBC, neutrophil, eosinophil, neutrophil/lymphocyte ratio (NLR), systemic inflammatory response index (SIRI), CRP/albumin ratio, CRP, albumin, PDW, RDW, MPV, and APTT were higher in the AUB group compared to the control group (p = 0.010, p = 0.002, p = 0.017, p = 0.017, p = 0.005, p = 0.003, and p < 0.001, respectively). Erythrocytes, hemoglobin, hematocrit, MCV, MCH, MCHC, fibrinogen, and INR were lower in the AUB group than in the control group (p < 0.001 for all). According to ROC analysis, RDW showed the highest diagnostic performance, with an AUC of 0.999 (p < 0.001). PDW and MPV also demonstrated high diagnostic values (AUC = 0.995 and AUC = 0.928, respectively) (p < 0.001). The NLR, SIRI, and CRP/albumin ratio had moderate diagnostic efficacy, with AUC values of 0.612, 0.640, and 0.642 (p = 0.022, p = 0.004, and p = 0.004, respectively). Conclusions: The high diagnostic performance of parameters such as RDW, PDW, and MPV in diagnosing AUB indicates that these parameters should be considered in clinical applications.